2010
DOI: 10.1007/s11104-010-0558-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of termite mound material on the physical properties of sandy soil and on the growth characteristics of tomato (Solanum lycopersicum L.) in semi-arid Niger

Abstract: This investigation assessed the effects of termite mound material (TMM) on the physical properties of sandy soil and on tomato (Solanum lycopersicum L.) growth characteristics and water use efficiency. TMM combined with organic manure, TMM combined with rice straw mulching and organic manure, organic manure alone (OM) and unamended (T0) were the treatments used. Results showed that soil treated with TMM had more clay sized particles and organic carbon content than T0 and OM. In TMM-treated soil, more water was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 31 publications
1
19
0
1
Order By: Relevance
“…After six years of amendment, CTS increased the organic C content in the soil because the waste has a high content of organic matter (Table 1). Our results are in agreement with those of others studies, which reported increased organic C contents after compost amendment (Garba, Cornelis, & Steppe, 2011;Arthur, Cornelis, & Razaghi, 2012). The soil pH increased after six years of CTS amendment, which is contrary to the general belief that organic residues decrease soil pH via the production of acids formed during the decomposition of organic matter.…”
Section: Resultssupporting
confidence: 92%
“…After six years of amendment, CTS increased the organic C content in the soil because the waste has a high content of organic matter (Table 1). Our results are in agreement with those of others studies, which reported increased organic C contents after compost amendment (Garba, Cornelis, & Steppe, 2011;Arthur, Cornelis, & Razaghi, 2012). The soil pH increased after six years of CTS amendment, which is contrary to the general belief that organic residues decrease soil pH via the production of acids formed during the decomposition of organic matter.…”
Section: Resultssupporting
confidence: 92%
“…; Garba et al . ). Although insignificant, bulk density of the top 0–5 cm was for all years lower for the treatments applied with manure than for C (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…Termites are dominant members of the soil arthropod community in all tropical ecosystems, and their biomass may represent up to 95% of the total soil arthropod abundance (Eggleton et al, 1998;Bignell & Eggleton, 2000). As ecosystem engineers, termites are responsible for large-scale bioturbation, soil aeration, and organic matter decomposition, altering physical, chemical, and biological properties of soils, which in turn affect plant growth and diversity (Garba et al, 2011;Van der Plas et al, 2013;Jouquet et al, 2015). The decomposition of complex organic matter into nutrients available for plants is one of the most important ecosystem services termites provide to tropical forests, which leads to ecosystem stabilisation under global change (Obi & Ogunkunle, 2009;Bonachela et al, 2015;Veldhuis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%